From Hormuz to Halmahera: Geopolitical Risk Transmission and Indonesia’s Energy–Food–Industry Nexus - Hanan Nugroho (The Journal of Indonesia Sustainable Development Planning, 2026)
Geopolitical tensions in the Middle East—particularly the confrontation between the United States and Iran—continue to exert a profound influence on global energy markets and broader macroeconomic stability. In an increasingly interconnected economy like Indonesia's, these dynamics generate cascading risks that extend beyond the energy sector, affecting food systems and industrial development. This commentary examines how potential disruptions in global oil supply, especially through strategic chokepoints such as the Strait of Hormuz, may transmit shocks to Indonesia’s energy security, food security, and nickel-based industrialization trajectory. Adopting an energy–food–industry nexus perspective, the paper demonstrates how external geopolitical shocks can propagate across interdependent sectors, thereby amplifying systemic vulnerabilities. While Indonesia’s expanding role in the global nickel value chain presents significant opportunities for downstream industrialization, persistent structural constraints remain, particularly due to dependence on imported energy inputs and exposure to global supply chain volatility. By integrating insights from energy geopolitics, industrial policy, and food security analysis, this paper offers a more comprehensive understanding of Indonesia’s development challenges in a turbulent global context. It concludes that strengthening national resilience requires a coordinated and forward-looking strategy, centered on energy diversification, the stabilization of food systems, and deeper industrial upgrading, in order to support a more robust and sustainable long-term development trajectory.